STABILITY INDICATING AND COST-EFFECTIVE ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF SOTORASIB BY USING RP-HPLC - YARLAGADDA, SUBBA RAO; MANNAM, SUBBA RAO; JAMPANI, BABY PADMINI (International Journal of Applied Pharmaceutics, 2021)
Objective: The current investigation was pointed at developing and progressively validating novel, simple, responsive and stable RP-HPLC method for the measurement of active pharmaceutical ingredient of Sotorasib. Methods: A simple, selective, validated and well-defined stability that shows isocratic RP-HPLC methodology for the quantitative determination of Sotorasib. The chromatographic strategy utilized symmetry C18 column of dimensions 150x4.6 mm, 3.5 µ, using isocratic elution with a mobile phase of acetonitrile and 0.1% orthophosphoric acid (70:30). A flow rate of 1 ml/min and a detector wavelength of 221 nm utilizing the PDA detector were given in the instrumental settings. Validation of the proposed method was carried out according to an international conference on harmonization (ICH) guidelines. Results: LOD and LOQ for the active ingredient were established with respect to test concentration. The calibration chart plotted was linear with a regression coefficient of R2>0.999, means the linearity was within the limit. Recovery, specificity, linearity, accuracy, robustness, ruggedness were determined as a part of method validation and the results were found to be within the acceptable range. Conclusion: The proposed method to be fast, simple, feasible and affordable in assay condition. During stability tests, it can be used for routine analysis of the selected drug.